Plasmacytoid dendritic cells in cutaneous sarcoidosis - Halawi, Ali; Kurban, Mazen; Abbas, Ossama (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
While absent from normal skin, plasmacytoid dendritic cells (pDCs) infiltrate the skin in several infectious, inflammatory, and neoplastic entities. In addition to providing anti-viral resistance, pDCs link the innate and adaptive immune responses. Sarcoidosis is an idiopathic multi-system granulomatous disease characterized by epitheliod granulomas. Its underlying immunopathogenesis involves hyperactivity of cell-mediated immune system with involvement of CD4+ T-helper cells of the Th1 subtype. Recently, pDCs have been shown to contribute to other cutaneous granulomatous disorders such as granuloma annulare (GA). Here, we intend to investigate pDC occurrence and activity in cutaneous sarcoidosis. Twenty cutaneous sarcoidosis cases and a comparable group of 20 cases of GA were retrieved from our database and were immunohistochemically tested for pDC occurrence and activity using anti-BDCA-2 and anti-MxA antibodies, respectively. Fifteen cases of cutaneous lupus erythrematosus (LE) were used as a comparison group. A semi-quantitative scoring system was used. pDCs were present in all cutaneous sarcoidosis in peri-vascular and/or peri-adnexal location admixed with lymphocytes. pDC numbers in sarcoidosis were comparable to those in GA, while pDCs were significantly more abundant in LE. MxA expression was mostly patchy in cutaneous sarcoidosis and GA cases, while LE cases showed diffuse and strong MxA expression. In conclusion, we have shown that pDCs are recruited into the skin lesions of sarcoidosis and GA. Despite the diminished type I IFN production demonstrated in our study, the consistent presence of pDCs in all cutaneous sarcoidosis cases speaks in favor of some role of these cells in the pathogenesis of granulomatous disorders.